(untitled) (International Journal of Engineering and Computer Science, 2017)
Growing convergence among mobile computing devices and embedded technology sparks the development and deployment of “context-aware” applications, where location is the most essential context. In this paper, we introduce a similar forensic surveillance tool for wireless networks. Our system, for wireless network can reveal the locations of WiFi-enabled mobile devices within the coverage area of a high-gain antenna. it features a mobile design that can be quickly deployed to a new location for instant usage without training. We present a comprehensive set of theoretical analysis and experimental results which demonstrate the coverage and localization accuracy of the design framework.